Α-decay study of Tl. (8th January 2016) - C Van Beveren,; Andreyev, A N; Barzakh, A E; Cocolios, T E; Groote, R P de; Fedorov, D; Fedosseev, V N; Ferrer, R; Ghys, L; Huyse, M; Köster, U; Lane, J; et al.
Abstract: α -decay spectroscopy of Tl has been performed at the CERN isotope separator on-line (ISOLDE) facility. New fine-structure α decays have been observed for both isotopes. α -decay branching ratios of 0.089(19)%, 0.047(6)% and 1.22(30)% have been deduced for the (10 − ), (7 + ) and (2 − ) states respectively in 184 Tl and a lower limit of 0.49% for the α -decay branching ratio of 182 Tl. A new half-life of 9.5(2) s for the (2 − ) state in 184 Tl and 1.9(1) s for the low-spin state in 182 Tl has been deduced. Using α – γ coincidence analysis, multiple γ rays were observed de-exciting levels in Au fed by Tl α decays. The γ transitions connecting these low-lying states in Au are essential to sort the data and possibly identify bands from in-beam studies in these isotopes. Owing to the complex fine-structure α decays and limited knowledge about the structure of the daughter nuclei, only partial level schemes could be constructed for both gold isotopes in the present work. Reduced α -decay widths have been calculated and are compared with values obtained in neighboring odd-A and even-A thallium isotopes. Except for the allowed α decay of the 184 Tl (10 − ) state, the other fine-structure α decays observed in this study are hindered. This points to strong structural changes between parent thallium and daughter gold isotopes.